Inventive thinking skills in science: A comparative study between students in Malaysia and Brunei - Maria, Abdullah; Kamisah, Osman (Common Ground Publishing, 2010)
In order to succeed in a digital economy, students will need digital age proficiencies. It is important for the educational system to make parallel changes in order to fulfil its mission in society, namely the preparation of students for the world beyond the classroom. Therefore, the educational system must understand and embrace the 21st century skills within the context rigorous academic standards. The main purposes of this study are to determine the inventive thinking skills in Science among students in Malaysia and Brunei and also to compare the inventive thinking skills of students in Science between Malaysia and Brunei. The dimension of inventive thinking skills is comprised of adaptability and managing complexity, self direction, curiosity, creativity, risk taking and higher order thinking and sound reasoning. This study which employed cross sectional surveys method involved 410 Primary school students from both countries.